Management of Self-Taught Learning for Non-Religious Background Students toward Culture Shock at State Islamic University - Syafnan Syafnan; Eka Putra; Yuserizal Bustami; Laila Surayya (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2023)
The purpose of this study was to explore the challenges of students from non-religious backgrounds when facing culture shock and highlight the management of self-taught learning carried out by students of one of the Islamic tertiary institutions in Bandung. This article used qualitative research method, a case study. Primary data source came from interviews with eight participants. The data analysis technique used was data condensation, data presentation, and drawing conclusions. The results showed that students with non-religious backgrounds who majored in religion at Islamic tertiary institutions experienced culture shock when participating in learning. The culture shock was in the form of being left behind in understanding the core theories of the department, due to their educational background coming from a public school. It required the students to start from zero compared to students with religious education backgrounds (Madrasah Aliyah and pesantren) who could directly participate in learning and deepen the knowledge. Based on the results of interviews with the respondents, the most common self-taught learning they did were study in their free time, study hard and study outside class hours, by reading books from various literacy.